Preparation method of integrated MXene / PDA-coated MF-EF solar steam generator with semi-cladding structure
By preparing an MXene/PDA photothermal conversion light-absorbing layer and assembling it with MF-EF, a semi-clad MXene/PDA@MF-EF solar steam generator is formed, which solves the problems of complex preparation and difficult thermal management in the existing technology, and achieves efficient seawater desalination and wastewater purification.
Patent Information
- Application Number
- CN202411530421.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
Existing solar-driven interfacial water evaporation technology suffers from complex preparation processes, lack of sustainability, and difficulties in coordinating thermal and water management, which affect its application in seawater desalination and wastewater purification.
MXene was prepared by HF etching and combined with dopamine polymer (PDA) to form an MXene/PDA photothermal conversion light-absorbing layer. It was then assembled with melamine sponge and polyethylene foam to form an MF-EF structure, thus forming an integrated MXene/PDA@MF-EF solar steam generator with a semi-cladding structure.
It achieves high photothermal conversion capability that is economical, scalable, and simple to prepare, and has good long-term stability and salt resistance. It can effectively carry out seawater desalination and wastewater purification, providing a feasible and stable solar water evaporation solution.
Smart Images

Figure CN119463282A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of seawater desalination and wastewater purification, and in particular to a method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure. Background Art
[0002] Water is the material basis for the survival and development of human society and is essential for people's healthy life. The total amount of water in the world is about 1.36 billion cubic kilometers, of which seawater accounts for more than 97%. The less than 3% of fresh water is also facing the problem of extremely uneven distribution. 68.7% of it is frozen in the polar ice caps and high-altitude glaciers, and the remaining 29.9% exists on the surface and in the permafrost. Less than 0.3% is directly available for human use. With the increasing shortage of global freshwater resources, it has become particularly urgent to seek economically effective and sustainable methods for freshwater production.
[0003] In recent years, solar-driven interfacial water evaporation technology has attracted widespread attention for its advantages of energy saving, environmental protection, pollution-free, and easy operation. It is considered to be an economical and effective strategy to alleviate the problem of fresh water shortage. As the core part of this system, photothermal conversion materials play an important role in it. So far, people have developed a variety of photothermal materials with different energy conversion principles for solar-driven water evaporation, but they still face problems such as complex preparation process, lack of sustainability, and limited practical application. In addition, in the design of evaporation systems, the coordinated control of thermal management (light absorption) and water management remains a huge challenge. From the perspective of practical applications, the development of economical, scalable, simple preparation process, high photothermal conversion capability and super hydrophilic evaporators is crucial to improving the overall performance of the evaporation system. Summary of the invention
[0004] According to the technical problems raised above, a method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure is provided. The MXene / PDA@MF-EF solar steam generator prepared by the present invention exhibits good long-term stability and salt resistance.
[0005] The technical means adopted by the present invention are as follows:
[0006] A method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure, comprising:
[0007] S1. Prepare MXene by HF etching method;
[0008] S2. Based on the prepared MXene, a MXene / PDA photothermal conversion light absorbing layer is prepared;
[0009] S3. Based on the prepared MXene / PDA, MXene / PDA@MF-EF was prepared.
[0010] Furthermore, step S1 specifically includes:
[0011] S11, add 40% HF and deionized water into a polytetrafluoroethylene beaker, weigh an appropriate amount of Ti3AlC2, slowly add it into the kettle and stir, wait for the reaction, and obtain a mixed slurry after the reaction is completed;
[0012] S12, centrifuging the mixed slurry until the pH value of the upper liquid is greater than 6 to obtain a precipitate;
[0013] S13, adding dimethyl sulfoxide to the obtained precipitate for reaction, washing and removing residual dimethyl sulfoxide after the reaction, centrifuging and drying the upper liquid to obtain few-layer and thin-layer MXene.
[0014] Further, step S2 specifically includes:
[0015] S21, adding dopamine hydrochloride and tris(hydroxymethyl)aminomethane to the aqueous suspension containing MXene;
[0016] S22, after stirring for 1 hour, the substrate was collected by centrifugation and dried to obtain MXene / PDA.
[0017] Furthermore, step S3 specifically includes:
[0018] S31, repeatedly washing and drying the melamine sponge and polyethylene foam with anhydrous ethanol;
[0019] S32, cutting the melamine sponge into a circle with a diameter of 32 mm and a height of 10 mm, and cutting the polyethylene foam into a circle with a diameter of 15 mm and a height of 5 mm;
[0020] S33, assembling the cut melamine sponge and polyethylene foam together to form MF-EPE Foam, which is named MF-EF;
[0021] S34, preparing a PVA / SA mixed solution, and soaking the sponge in the PVA / SA mixed solution;
[0022] S35, after soaking, in Ca 2+ and cross-linked in glutaraldehyde solution, and washed and dried with deionized water;
[0023] S36. Coat MXene / PDA on the surface of MF-EF to form MXene / PDA@MF-EF.
[0024] Furthermore, the centrifugal condition in step S12 is 5000 r / s for 5 min.
[0025] Furthermore, the drying condition in step S13 is 40°C.
[0026] Furthermore, the stirring temperature condition in step S22 is 30°C.
[0027] Furthermore, the temperature condition for preparing the PVA / SA mixed solution in step S34 is 90°C.
[0028] Furthermore, in step S35, Ca 2+ The concentrations of the glutaraldehyde solution were 1 wt% and 2 wt%, respectively.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] 1. The present invention provides a method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure, which can be applied to seawater desalination and wastewater purification.
[0031] 2. The integrated MXene / PDA@MF-EF solar steam generator prepared by the method of the present invention exhibits good long-term stability and salt resistance.
[0032] 3. Considering the economic, scalable and simple preparation process of MXene / PDA@MF-EF, the MXene / PDA@MF-EF evaporator achieves clean water production through the coordinated effects of thermal management and water management, providing a feasible and stable alternative for solar water evaporation in various water environments.
[0033] 4. The preparation method of an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure provided by the present invention provides a solution to the problem of obtaining fresh water in coastal areas, offshore islands and other areas by realizing solar-driven interfacial evaporation desalination technology, and provides a new approach for the rational design of new photothermal conversion materials.
[0034] Based on the above reasons, the present invention can be widely promoted in the fields of seawater desalination and wastewater purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0036] Figure 1The figure is a preparation roadmap of the MXene / PDA and MXene / PDA@MF-EF evaporators with excellent light-to-heat conversion capabilities of the present invention.
[0037] Figure 2 This is a scanning electron microscope image of Ti3AlC2 provided in an embodiment of the present invention.
[0038] Figure 3 This is a scanning electron microscope image of the MXene provided in an embodiment of the present invention.
[0039] Figure 4 This is a scanning electron microscope image of MXene / PDA provided in an embodiment of the present invention.
[0040] Figure 5 This is a transmission electron microscope image of MXene / PDA provided in an embodiment of the present invention.
[0041] Figure 6 This is a diagram showing the MF provided in an embodiment of the present invention under a scanning electron microscope.
[0042] Figure 7 This is a diagram showing the MF-EF provided in an embodiment of the present invention under a scanning electron microscope.
[0043] Figure 8 This is a scanning electron microscope image of MXene / PDA@MF-EF provided in an embodiment of the present invention.
[0044] Fig. 9 A side-cut view of the PCC-MXene / Ag3PO4 mixed membrane provided in an embodiment of the present invention.
[0045] Fig.10 This is a transmission electron microscope image of MXene / PDA@MF-EF provided in an embodiment of the present invention.
[0046] Fig.11 Embodiments of the present invention provide for detecting the presence of different elements.
[0047] Fig.12 Before and after comparison of pressing white paper onto the surface of MXene / PDA@MF-EF provided in an embodiment of the present invention.
[0048] Fig.13 The contact angle of MXene / PDA@MF-EF provided in an embodiment of the present invention.
[0049] Fig.14 Water transfer rate / PDA@MF-EF of MXene provided in an embodiment of the present invention.
[0050] Fig.15 The weight change of MXene / PDA@MF-EF before and after water absorption provided by an embodiment of the present invention.
[0051] Fig.16 This is the wet thermal conductivity of MXene / PDA@MF-EF provided in an embodiment of the present invention.
[0052] Fig.17 Schematic diagram of a simulated sunlight seawater desalination test device provided in an embodiment of the present invention.
[0053] Fig.18 UV-Vis-NIR spectra of MF-EF and MXene provided in the embodiments of the present invention
[0054] / PDA@MF-EF.
[0055] Fig.19 The 1kW m provided in the embodiment of the present invention -2 Changes in illumination water quality over time.
[0056] Fig. 20 The 1kW m provided in the embodiment of the present invention -2 Variation of illumination water quality with evaporation rate and efficiency.
[0057] Fig.21 A comparison chart of evaporation rates and efficiencies of different evaporation systems under sunlight provided by an embodiment of the present invention.
[0058] Fig. 22 The MXene / PDA@MF-EF provided in the embodiment of the present invention has a -2 Result graph of 10 cycles of testing in pure water under illumination.
[0059] Fig.23 Schematic diagram of the salt resistance of the MXene / PDA@MF-EF solar evaporator for seawater desalination provided in an embodiment of the present invention.
[0060] Fig.24 Schematic diagram of salt deposition on the evaporator surface provided by an embodiment of the present invention.
[0061] Fig.25 The mass change curve of the evaporator provided in the embodiment of the present invention under different concentrations of brine over time.
[0062] Fig.26 The evaporation rate and evaporation efficiency of the evaporator provided in the embodiment of the present invention under different concentrations of brine.
[0063] Fig. 27 The mass change of MXene / PDA@MF-EF provided in an embodiment of the present invention after continuous evaporation for 6 hours in artificial seawater.
[0064] Fig.28 The evaporation efficiency and rate of MXene / PDA@MF-EF provided in an embodiment of the present invention after continuous evaporation for 6 hours in artificial seawater.
[0065] Fig.29 This is a graph showing the stability test results of MXene / PDA@MF-EF provided in an embodiment of the present invention after evaporation in seawater for 7 days.
[0066] Fig.30 The resistance values before and after seawater desalination provided by the embodiment of the present invention.
[0067] Fig.31 The ion concentration before and after seawater desalination provided by the embodiment of the present invention.
[0068] Fig.32 The interception rate provided by the embodiment of the present invention.
[0069] Fig.33 Photos of the MXene / PDA@MF-EF pH test paper provided in an embodiment of the present invention before and after evaporation in acidic / alkaline water.
[0070] Fig.34 The UV-visible absorption peak and color change diagram of the dye molecule before and after purification provided in the embodiment of the present invention.
[0071] Fig.35 An outdoor evaporation device made of polymethyl methacrylate is provided in an embodiment of the present invention.
[0072] Fig.36 The photos provided for the embodiments of the present invention show pictures of outdoor devices when exposed to natural sunlight for 60 minutes.
[0073] Fig.37 The embodiment of the present invention provides a process of droplet formation on the upper surface of a device irradiated with natural sunlight for 0 to 60 minutes.
[0074] Fig.38 The present invention provides an experiment of outdoor light intensity and ambient temperature and humidity curve from 9:00 to 18:00.
[0075] Fig.39 A graph showing changes in water quality of water samples collected at different times under natural light provided in an embodiment of the present invention.
[0076] Fig.40 The water production for 5 consecutive days provided by the embodiment of the present invention.
[0077] Fig.41 This is a comparison chart of the 15-day cultivation of water lilies using seawater and purified water provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0078] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0079] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0080] Example 1
[0081] Preparation of MXene and MXene / PDA:
[0082] 1. Prepare MXene using HF etching method;
[0083] In the specific implementation, as a preferred embodiment of the present invention, MXene is prepared by using HF etching method, which specifically includes:
[0084] First, add 20mL40%HF+15mL deionized water into a 100mL polytetrafluoroethylene beaker, weigh 2gTi3AlC2 and slowly add it into the kettle, and react at 40 degrees for 10 to 12 hours; after the reaction, centrifuge the above slurry at 5000rpm for 5min until the pH value of the upper liquid is greater than 6, then take 25mL dimethyl sulfoxide (DMSO) and add it to the above precipitate and stir at room temperature for 12h. After the reaction, wash 3 times to remove residual DMSO. After centrifugation, the upper liquid is a single-layer MXene dispersion, and the lower precipitate is dried in a vacuum drying oven at 40 degrees to obtain a few layers and thin layers of MXene.
[0085] Among them, hydrofluoric acid (HF) is highly corrosive and selectively etches the Al layer to obtain lamellar nanosheets. And HF should be added slowly to avoid excessive addition to cause local oxidation and thus produce TiO2.
[0086] 2. Based on the prepared MXene, prepare the MXene / PDA photothermal conversion light absorbing layer;
[0087] In specific implementation, as a preferred embodiment of the present invention, based on the prepared MXene, a MXene / PDA light-to-heat conversion light-absorbing layer is prepared, which specifically includes:
[0088] 50 mg of dopamine hydrochloride and 100 mg of tris(hydroxymethyl)aminomethane were added to 125 mL of an aqueous suspension containing MXene (4 mg g-1), stirred at 30 °C for 1 h, centrifuged at 8000 rpm for 5 min, and the substrate was collected, centrifuged and dried at 40 °C. Figure 1 As shown in (a), MXene / PDA is finally obtained;
[0089] like Figure 2 As shown in the SEM image, it can be seen that the original Ti3AlC2 is a loose block structure. After selective etching by HF, the following is obtained: Figure 3 The accordion-like sheet structure shown in the figure shows that the etching degree is good and the sheet distribution is relatively uniform after magnification, indicating that the MXene has been successfully prepared. Figure 4 As shown, polydopamine was in situ polymerized on the MXene surface. Figure 3 By comparison, it can be found that evenly distributed particles appear on the MXene surface, indicating the successful preparation of the MXene / PDA composite material. Figure 5 As shown, the TEM image clearly shows the MXene layer structure and the granular PDA evenly distributed on the surface. After high-power projection electron microscopy, clear lattice fringes can be seen. The lattice spacing is measured to be 0.48nm, indicating that MXene / PDA has good crystallinity and is stable.
[0090] Example 2
[0091] Preparation of an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure
[0092] 1. Preparation of MXene by HF etching method; (same preparation process as in Example 1)
[0093] 2. Based on the prepared MXene, a MXene / PDA photothermal conversion light absorbing layer is prepared; (the preparation process is the same as that in Example 1)
[0094] 3. Based on the prepared MXene / PDA, MXene / PDA@MF-EF was prepared.
[0095] First, MF and EPE foams were repeatedly rinsed and dried with anhydrous ethanol, and MF was cut into a circle with a diameter of 32 mm and a height of 10 mm, and EPE foam was cut into a circle with a diameter of 15 mm and a height of 5 mm. The two were assembled together to form MF-EPEFoam, which was named MF-EF. Then, a PVA / SA mixture was prepared. 1 g of PVA powder and 1 g of SA powder were added to 100 mL of deionized water and heated at 90 ° C for 1 h. The sponge was immersed in the PVA / SA mixture for 1 h and then in 1 wt% Ca 2+ After cross-linking for 30 min, the MF-EF was immersed in a 2 wt% glutaraldehyde solution for 120 min, washed with deionized water and dried, and finally 50 mg MXene / PDA was coated on the surface of the MF-EF. Figure 1 b Formation of MXene / PDA@MF-EF. In this example, the total size of the prepared MXene / PDA@MF-EF solar evaporator is 0.1 cm in height and 3.2 cm in diameter.
[0096] like Figure 6 As shown in the figure, it can be seen that the original PVDF surface is smooth and the surface porosity is not obvious. Figure 7 As shown in the figure, it can be seen that the surface of PCC-MXene / Ag3PO4 becomes rough and the surface porosity is better than that of PVDF membrane, but the porosity is still low. Figure 8 As shown in Figure 2, after adding CaCO3 to PCC-MXene / Ag3PO4 and immersing the membrane in HCl to release CO2, the surface of PCC-MXene / Ag3PO4 becomes rough and the pores are richly distributed. Fig. 9 As shown in the figure, it is a side-cut view of the PCC-MXene / Ag3PO4 mixed membrane. It can be seen that the addition of PEG helps to form vertical channels on the side of the membrane. Therefore, after modification with CaCO3 and PEG, the PCC-MXene / Ag3PO4 mixed membrane has laid a good foundation for the absorption of interfacial evaporative light and water transmission due to its rich pore structure and excellent water transmission channels.
[0097] like Figure 6 It is clear that the original melamine foam (MF) has an open macroporous structure composed of a macroscopically ordered three-dimensional skeleton, and the three-dimensional skeleton is actually constructed by three-dimensional interconnected microfibers with smooth surfaces. MF-EP is formed by immersion modification of PVA / SA and embedding in 3DEPE foam, such as Figure 7 As shown in Figure 2, SEM analysis of the upper surface of MF-EP revealed that after being modified by PVA / SA immersion, the original skeleton structure of MF was still retained, and the rough surface between the skeletons was attributed to the effective attachment of the flake gel produced by PVA / SA to the MF surface. In order to enhance its light absorption ability, MXene / PDA was coated on the surface of MF-EF, as shown in Figure 2. Figure 8 As shown in Figure 2, MXene / PDA is uniformly attached to the surface of the sheet-like aerogel produced by PVA / SA, indicating the successful preparation of the MXene / PDA@MF-EF composite. Fig.11 As shown in the figure, through EDS Mapping, the Ti element in MXene and the N element in PDA, as well as the Ca element in the cross-linking agent, can be detected. 2+ The presence of , therefore, further indicates the successful preparation of MXene / PDA@MF-EF composites.
[0098] like Fig.12 As shown in the figure, a white paper is pressed on the surface of MXene / PDA@MF-EF. By comparing the images of the paper before and after pressing, it can be found that there is no black MXene / PDA adhered to the paper before and after pressing. The surface is firmly coated on the surface of MF-EF and is well combined with MF-EF through the action of intermolecular hydrogen bonds. However, the interfacial evaporation performance driven by solar energy is also affected by the wettability of the material. Therefore, the hydrophilicity of MXene / PDA@MF-EF was tested by the contact angle, as shown in Figure 1. Fig.13 As shown in the figure, it can be found that the water is completely absorbed within 215ms, and the surface material has excellent hydrophilicity. Fig.14 It can be found that when a piece of paper is placed on the surface of MXene / PDA@MF-EF material, it can be seen that the paper is completely soaked within 20 seconds, indicating that MXene / PDA@MF-EF has excellent water transmission channels and transmission rates. Then, the weight change of MXene / PDA@MF-EF before and after water absorption was tested with an analytical electronic balance, as shown in Figure 2. Fig.15 As shown, it can be found that the water retention capacity of MXene / PDA@MF-EF can reach 13.7281 g, which is convenient for the storage and transportation of water during evaporation.
[0099] Example 3
[0100] The prepared integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure was used in simulated seawater desalination and wastewater purification.
[0101] (1) The MXene / PDA@MF-EF prepared in Example 2 was placed in different simulated water environments (pure water) and heated to 1 sun (1 kW / m 2 ) for 60 minutes. The evaporation performance was tested using the laboratory's simulated solar test device system. During the test, the solar-driven seawater desalination test device ( Fig.17The device consists of several main parts: a xenon lamp (simulating sunlight), an electronic balance (recording the mass of water molecules during evaporation), an infrared thermal imager (testing the surface temperature of the material), and a computer (electronic balance data receiver). The evaporation rate and evaporation efficiency of MXene / PDA@MF-EF can be obtained based on the slope of the curve of mass change over time, and the evaporation cycle efficiency of MXene / PDA@MF-EF was tested for 10 times under one sun.
[0102] The changes in the surface temperature of MXene / PDA@MF-EF during the reaction were recorded using an infrared thermal imager. Fig.17 As shown in the simulated 3D cross-sectional view on the left, the 3D embedded EPE foam acts as an insulation layer to minimize heat transfer to the bottom water. During the evaporation process, a 2D water transmission channel is formed in the 3D thin layer around the EPE foam, ensuring sufficient water supply to the heated surface. At the same time, due to the surface MXene / PDA light-absorbing layer, the sponge can quickly convert the absorbed sunlight into heat to generate a temperature gradient, thereby exhibiting excellent photothermal conversion capabilities and effectively achieving water evaporation. However, since the surface light absorption capacity of MXene / PDA@MF-EF has a direct impact on the evaporation performance of the material, the solid UV diffuse reflectance spectroscopy was used to test the absorbance of MF-EF and MXene / PDA@MF-EF before and after coating with MXene / PDA, as shown in the figure. Fig.18 As shown in the figure, the maximum absorbance of MXene / PDA@MF-EF in the range of 200-2500nm can reach about 96%, indicating that MXene / PDA@MF-EF has good light absorption ability. Fig.19 As shown in Figure 2, the mass change of water during evaporation of pure water, MF, MF-EF and MXene / PDA@MF-EF was tested under dark conditions and under simulated sunlight conditions. Fig. 20 As shown in Figure 2, their evaporation rates calculated by photothermal conversion are 0.6636, 0.7272, 0.8982 and 1.5576 kg m -2 h -1 , the photothermal conversion efficiency is 33.26%, 37.45%, 48.73% and 93.35% (the calculation formula is shown in the Supporting Information). The evaporation rate of MXene / PDA@MF-EF is comparable to that of previous literature (e.g. Fig.21 ), the solution of the present invention still shows some advantages. Finally, in order to evaluate the evaporation stability of MXene / PDA@MF-EF, Fig. 22 As shown, its 10 cycle stability tests in pure water were tested under a simulated light intensity of 1 kW m-2 (the insets are the mass change diagrams for cycles 1, 5, and 10, respectively), and it was concluded that MXene / PDA@MF-EF has good cycle stability in pure water.
[0103] (2) Using a xenon lamp to simulate sunlight, salt tolerance tests were conducted on salt water with different concentrations;
[0104] Simulated seawater, 5wt%, 10wt% and 20wt% NaCl solutions were used as test seawater with different concentrations. -2 Under illumination (light intensity 100mW cm -2 ) Test the photothermal evaporation performance of MXene / PDA@MF-EF in salt solutions with different NaCl contents.
[0105] In actual seawater desalination applications, the composition of seawater is complex, and a large amount of salt will be deposited on the surface of the evaporator during the evaporation process, thus affecting its performance. Therefore, the evaporator needs to have excellent salt resistance to maintain efficient operation of the evaporator. To this end, this example studies the photothermal evaporation performance of MXene / PDA@MF-EF in salt solutions with different NaCl contents. First, Fig.23 The figure shows the schematic diagram of the salt resistance of MXene / PDA@MF-EF as a solar evaporator. Due to the regularly arranged porous structure inside MXene / PDA@MF-EF, water is continuously evaporated into water vapor through the pore structure. As the evaporation proceeds, the salt concentration in the upper part of the evaporator is higher than that in the lower part, thereby forming a salt concentration gradient inside the evaporator. According to the principle of osmosis, this concentration difference will drive low-salt concentration water molecules to diffuse to high-salt concentration areas. When low-salt concentration water molecules enter the high-salt concentration area through the pore structure of the evaporator, they will interact with salt molecules in the high-salt concentration area, causing the water in the high-salt concentration area to be "diluted" by the low-salt concentration water, so that the evaporation and dilution of seawater are in a dynamic equilibrium state, thereby achieving an effective salt resistance effect.
[0106] In order to further study the salt tolerance of MXene / PDA@MF-EF, Fig.24 As shown in the figure, 0.5g of salt particles were placed on the surface of MXene / PDA@MF-EF and all the surface salt particles dissolved in water within 140min. This result shows that the MXene / PDA@MF-EF evaporator has excellent hydrophilicity and macroporous structure, which can quickly dissolve the salt particles. However, the slightly longer dissolution time may be because after MXene / PDA is coated on the surface as a light-absorbing layer, the surface pore size and hydrophilicity are slightly reduced, resulting in a slowdown in the initial dissolution rate of the salt particles. In addition, during the experiment, the uneven distribution of salt particles on the sample surface may also have affected the dissolution time.
[0107] In summary, despite these factors, MXene / PDA@MF-EF materials still exhibit good salt resistance.
[0108] In order to further test the salt tolerance of MXene / PDA@MF-EF during brine evaporation, the -2 The evaporation performance of MXene / PDA@MF-EF in simulated seawater and NaCl solutions of different concentrations was tested under light intensity of . Fig.25 As shown in the figure, the mass change of MXene / PDA@MF-EF gradually decreases with the increase of salt concentration, indicating that high salt concentration has a certain effect on the transport of water molecules. Fig.26 The calculation results show that the evaporation rates of MXene / PDA@MF-EF in pure water, simulated seawater, 5wt%, 10wt%, and 20wt% NaCl solutions are 1.5576, 1.5228, 1.4994, 1.4664, and 1.4190 kg m -2 h -1 The evaporation efficiencies were 93.35%, 91.05%, 89.51%, 86.72% and 84.22% respectively. The above results show that the evaporation rate and efficiency of MXene / PDA@MF-EF decrease slightly with the increase of salt solution concentration, but even in 20wt% NaCl solution, the photothermal evaporation rate and efficiency can still reach 1.419kg m -2 h -1 and 84.22%, thus showing good salt resistance. However, the salt resistance and long-term stability of MXene / PDA@MF-EF during evaporation are crucial in the actual evaporation process. Figure 27-28 As shown in the figure, MXene / PDA@MF-EF was subjected to a continuous evaporation test for 6 h. After continuous evaporation for 8 h in a 3.5 wt% solution, it was still able to maintain a high evaporation rate, indicating that MXene / PDA@MF-EF has good salt resistance and stability. However, in order to ensure the reusability of the MXene / PDA@MF-EF evaporator in seawater, as shown in the figure, Fig.29 As shown, at 1kW m -2 A continuous evaporation experiment was carried out in 3.5wt% NaCl solution under light for 7 days, and a group of evaporation efficiency was tested every day. The results showed that MXene / PDA@MF-EF can still maintain a high evaporation rate after long-term use. From the comparison pictures of the MXene / PDA@MF-EF surface after evaporation for 1 day and 7 days, it can be seen that the surface structure of the material is intact.
[0109] The above results show that MXene / PDA@MF-EF has good salt resistance and cyclic stability durability.
[0110] (3) Using xenon lamps to simulate sunlight, seawater and wastewater purification experiments were conducted on organic dyes (MB, RhB, and MO), acidic and alkaline wastewater, and simulated seawater;
[0111] At 1kW m -2 Under illumination (light intensity 100mW cm -2 ) Test anti-fouling performance;
[0112] Since MXene / PDA@MF-EF has good stability, in order to further confirm
[0113] The applicability of MXene / PDA@MF-EF evaporator in treating various water sources, so several representative water sources were used to produce fresh water, including seawater, acid / base solution and dye-contaminated water. The MXene / PDA@MF-EF evaporator was used to test the evaporation and desalination of seawater, and then the changes in the concentration of metal ions in the solution before and after seawater desalination were tested by multimeter resistance value and ICP. Fig.30 As shown in the figure, it can be found that the resistance value of seawater is 97.3KΩ, and the resistance value of the collected water after desalination is 2.4MΩ, which is close to the resistance value of daily drinking water (2.3MΩ). Fig.31 As shown in the figure, Na in seawater after desalination + Mg 2+ , K + and Ca 2+ The concentration of 2-3 orders of magnitude has been significantly reduced, reaching the standards set by the World Health Organization (WHO). Fig.32 As shown in the figure, it can be found that the retention rate of MXene / PDA@MF-EF for several metal ions is close to 100%. The pH value of the water collected by MXene / PDA@MF-EF under both acidic and alkaline solution conditions is close to ( Fig.33 ), indicating that MXene / PDA@MF-EF has good acid and alkali resistance. Finally, the dye-contaminated water source was evaporated, such as Fig.34 As shown, the water collected after evaporation over a period of time is nearly colorless and transparent, and UV-vis spectroscopy confirms that there is almost no dye remaining.
[0114] The above results show that in addition to having good desalination and purification performance for seawater, MXene / PDA@MF-EF also has good purification capabilities for a variety of water sources.
[0115] (4) The MXene / PDA@MF-EF evaporator was placed in an outdoor evaporation device built using a homemade device made of polymethyl methacrylate, and the outdoor solar evaporation performance of the MXene / PDA@MF-EF evaporator was studied by taking into account actual environmental change factors.
[0116] In order to verify the actual solar evaporation performance of the MXene / PDA@MF-EF evaporator, an outdoor evaporation device was built using a homemade device made of polymethyl methacrylate to study the outdoor solar evaporation performance of the MXene / PDA@MF-EF evaporator.
[0117] like Fig.35 As shown, the upper part of the device consists of a hemispherical steam condenser for condensing fresh water, the middle part consists of a cylindrical evaporation chamber and a serrated support plate for supporting the evaporator, and the bottom consists of a concave water collection chamber and a water collection pipe for collecting fresh water flowing out of the top condenser. Four circular MXene / PDA@MF-EF evaporators with a diameter of 31 mm were selected and placed in the evaporation chamber. A 9-hour outdoor natural light seawater desalination experiment was conducted outdoors at the Linghai Campus of Dalian Maritime University from 9:00 am to 18:00 pm (seawater was taken from the Bohai Sea in China). At 09:00, no droplets were generated on the steam condenser, and water mist began to form on the surface after 10 minutes of irradiation ( Fig.37 ) and within 1h of irradiation ( Fig.36 , 37), obvious small droplets form on the inner wall of the spherical steam condenser. Fig.38 As shown in the figure, the ambient temperature and humidity change with the light exposure time. The maximum radiation intensity on that day is 84.7kW m -2 The high ambient temperature is 42.5℃ and the corresponding humidity is 10.6%. The change trend of solar radiation is also consistent with the temperature change curve, while the change of ambient humidity is opposite to the temperature curve. Fig.39 The evaporation performance of MXene / PDA@MF-EF is shown in Figure 2. The changes in the mass of water molecules at 12:00, 15:00, and 18:00 are 2.826, 5.579, and 7.170 kg m -2 The results show that the maximum water production in 9 hours can reach 7.170 kg m -2 . Accordingly, 1m 2 The water output of the device can meet the daily water needs of 2 adults (the basic daily water requirement of adults is 2.5L). Fig.40 As shown in the figure, after 5 days of outdoor evaporation water production results, it was found that the overall trend of changes in light intensity and ambient temperature and humidity was consistent with that on the first day, and the overall water production rate on sunny days was higher than that on cloudy days, indicating that the water production rate was mainly affected by the intensity of solar radiation. It is worth noting that compared with indoor solar radiation evaporation, the outdoor solar radiation evaporation rate is lower than the indoor evaporation rate, which is mainly attributed to the lower outdoor irradiation intensity. Obviously, in order to increase the actual fresh water production from solar energy, it is important to develop an evaporation system that provides excellent light absorption and accelerates the condensation of water droplets. Finally, in order to further evaluate the non-toxicity of desalinated water, 16 water lily seeds were selected and placed in water directly taken from the Bohai Sea and purified Bohai Sea water and cultivated at room temperature. As Fig.41As shown, after 15 days of continuous observation, it was found that the water lilies in seawater did not sprout after 15 days of cultivation, while the water lilies cultivated in desalinated seawater sprouted on the seventh day, and as time went on, the sprouts gradually grew longer and always maintained a good growth state.
[0118] The above results demonstrate that the MXene / PDA@MF-EF evaporator has broad application potential in fresh water production.
[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure, characterized in that: include: S1. Prepare MXene by HF etching method; S2. Based on the prepared MXene, a MXene / PDA photothermal conversion light absorbing layer is prepared; S3. Based on the prepared MXene / PDA, MXene / PDA@MF-EF was prepared.
2. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: Step S1 specifically includes: S11, add 40% HF and deionized water into a polytetrafluoroethylene beaker, weigh an appropriate amount of Ti3AlC2, slowly add it into the kettle and stir, wait for the reaction, and obtain a mixed slurry after the reaction is completed; S12, centrifuging the mixed slurry until the pH value of the upper liquid is greater than 6 to obtain a precipitate; S13, adding dimethyl sulfoxide to the obtained precipitate for reaction, washing and removing residual dimethyl sulfoxide after the reaction, centrifuging and drying the upper liquid to obtain few-layer and thin-layer MXene.
3. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: Step S2 specifically includes: S21, adding dopamine hydrochloride and tris(hydroxymethyl)aminomethane to the aqueous suspension containing MXene; S22, after stirring for 1 hour, the substrate was collected by centrifugation and dried to obtain MXene / PDA.
4. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: Step S3 specifically includes: S31, repeatedly washing and drying the melamine sponge and polyethylene foam with anhydrous ethanol; S32, cutting the melamine sponge into a circle with a diameter of 32 mm and a height of 10 mm, and cutting the polyethylene foam into a circle with a diameter of 15 mm and a height of 5 mm; S33, assembling the cut melamine sponge and polyethylene foam together to form MF-EPE Foam, which is named MF-EF; S34, preparing a PVA / SA mixed solution, and soaking the sponge in the PVA / SA mixed solution; S35, after soaking, in Ca 2+ and cross-linked in glutaraldehyde solution, and washed and dried with deionized water; S36. Coat MXene / PDA on the surface of MF-EF to form MXene / PDA@MF-EF.
5. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: The centrifugal condition in step S12 is 5000 r / s for 5 min.
6. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: The drying condition in step S13 is 40°C.
7. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: The stirring temperature condition in step S22 is 30°C.
8. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: The temperature condition for preparing the PVA / SA mixed solution in step S34 is 90°C.
9. The method for preparing an integrated MXene / PDA@MF-EF solar steam generator with a semi-cladding structure according to claim 1, characterized in that: In step S35, 2+ The concentrations of the glutaraldehyde solution were 1 wt% and 2 wt%, respectively.
Citation Information
Cited By
Preparation method of efficient water evaporation MXene-CuS pyramid array photo-thermal structure
CN120681823A